Study of stability during vortex-induced rotational vibrations at moderate Reynolds number using an immersed-boundary finite element technique - Cruchaga-Ssa., M (EMERALD GROUP PUBLISHING LTD, 2026)
PurposeThis work is devoted to validating a proposed finite element method with an immersed boundary technique for dealing with fluid-structure problems. Particularly, this study aims to investigate the vortex-induced vibration in pitching mode for flow past a cylinder with a NACA0012 cross-section at Re = 1000.Design/methodology/approachThe numerical technique for solving fluid-structure interaction problems is described in the framework of a fixed-mesh finite element method. The solid motion is computed via the momentum equation for rotations. The solid velocity is imposed on the fluid as a restriction on the current fluid-solid immersed interface via a penalty technique. An exhaustive validation is first made by comparing the computed boundary layers and hydrodynamic coefficients (drag, lift, pressure and friction coefficients) on fixed cylinders with other numerical techniques. After that, the induced pitching problem is studied.FindingsThe analysis provides valuable information on the resulting fluid-structure interactions and the system s stability. The results highlight the emergence of vortex shedding and its interaction with the structure, along with the role of aerodynamic damping in shaping the dynamic behavior. The findings consolidate the use of the proposed technique for the problem studied.Originality/valueThe novel aspects of this study encompass: the implemented immersed boundary formulation for rotational motion; the detailed evaluation of hydrodynamic coefficients and boundary layer evolutions; the evaluation of system stability under pitch response by varying mass ratios and torsional stiffness; and the provided exhaustive comparison with other numerical methods.